(untitled) (GAIMS Journal of Medical Sciences, 2023)
Hypertrophic cardiomyopathy (HCM) is a genetic disorder characterized by left ventricular hypertrophy not explained by secondary causes, and a non-dilated left ventricle with preserved or increased ejection fraction. It is commonly asymmetric with most severe hypertrophy involving the basal interventricular septum.. The histologic features of HCM are myocyte hypertrophy and disarray, as well as interstitial fibrosis. The hypertrophy is associated with left ventricular diastolic dysfunction. Left ventricular outflow tract obstruction is present at rest in about one third of the patients, and can be provoked in another third. HCM is also an important cause of sudden cardiac death, particularly in adolescents and young adults. Nonsustained ventricular tachycardia, syncope, a family history of sudden cardiac death, and severe cardiac hypertrophy are major risk factors for sudden cardiac death.incidence being 30 % and the cause of cardiac death is LVOT obstruction,increased oxygen of thick myocardium with compromised coronary circulation and intractable ventricular tachycardia. Mutations in over a dozen genes encoding sarcomere-associated proteins cause HCM. MYH7 and MYBPC3, encoding β-myosin heavy chain and myosin binding protein C, respectively, are the two most common genes involved, together accounting for about 50% of the HCM families. Mutations in genes responsible for storage diseases cause a phenotype like HCM (genocopy or phenocopy). The routine applications of genetic testing and preclinical identification of family members represents an important advance. In genetic study HCM is associated with HLA DRW4